Comparative Study of Emotional Intelligence and Coping Styles in Orphans and Non-Orphan Adolescents in Delhi/NCR Region - Aahana Singh; Dr. Shruti Datt (International Journal of Indian Psychȯlogy, 2022)
This study investigated the emotional intelligence (EI) and coping strategies of adolescent orphans in comparison to non-orphans. The study included a total of 105 adolescents, consisting of 60 non-orphans along with 45 orphans using purposive sampling method. There were no statistically significant differences in coping, emotional intelligence, emotion-focused coping, or avoidant coping between the two groups. The findings indicate that both orphans and non-orphans may demonstrate identical levels of emotional intelligence (EI) and coping methods. Further investigation with a variety of samples is required to validate these findings. The study enhances our comprehension of emotional well-being in adolescent orphans and proposes that therapeutic therapies may not need to be significantly modified just based on the fact that the individual is an orphan. Nonetheless, it is essential to tailor interventions based on individual requirements and cultural circumstances.